Development of astaxanthin-loaded layer-by-layer emulsions: physicochemical properties and improvement of LPS-induced neuroinflammation in mice. Issue 12 (12th May 2021) - Zhao, Tong; Ma, Dexue; Mulati, Aiziguli; Zhao, Beita; Liu, Fuguo; Liu, Xuebo
Abstract : Astaxanthin-loaded emulsions were formed using heat-treated lactoferrin and polysaccharides, and the optimized emulsion could effectively inhibit neuroinflammation and learning-memory loss in C57BL/6J mice. Abstract : Astaxanthin (AST) has been shown to have neuroprotective effects; however, its bioavailability in vivo is low due to its hydrophobic properties. In this study, lactoferrin (LF) was prepared by heat-treatment at different temperatures, and on this basis, a layer-by-layer self-assembly method was used to construct double-layer emulsions with LF as the inner layer and polysaccharide (beet pectin, BP or carboxymethyl chitosan, CMCS) as the outer layer. Then AST was encapsulated in the emulsions and their physiochemical properties and function were investigated. The results indicated that high temperature heated LF (95 °C) showed a more stable structure than the lower temperature one, and the exposed internal nonpolar groups of LF could give the emulsion an enhanced stability. The rheology results showed that compared with CMCS, the double-layer emulsion formed by BP had a higher viscosity. In addition, the 95 °C LF–AST–BP emulsion showed the best stability among all the bilayer emulsions. The best emulsion was then used as a model drug to investigate its effects on lipopolysaccharide (LPS)-induced neuroinflammation and learning-memory loss in C57BL/6J mice. Through animal behavioral experiments, it was found that dietary supplementation with the AST emulsion could effectively improve the brain cognitive and learning memory impairment caused by inflammation. Transmission electron microscopy, mRNA and western blotting results also illustrated that the AST emulsion could alleviate neuroinflammation caused by LPS. This study provides a feasible scheme for exploring an AST loaded system and may be suitable for food and drug applications.